2011
DOI: 10.1007/s00296-011-1816-z
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-associated spinal osteoporosis treated with bisphosphonates: long-term follow-up of maternal and infants outcome

Abstract: Pregnancy-associated spinal osteoporosis (PPSO) is a rare condition characterized by severe back pain occurring near the end of the first pregnancy or shortly afterward. The aim of this report is to present a 12-year follow-up of a patient with PPSO. Also, the outcomes of patient's two pregnancies and her infants after long-term treatment with bisphosphonates are assessed. A young woman was referred to our tertiary care hospital aged 30 years, due to intense pain in thoracic and lumbar region that started duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 18 publications
0
12
0
2
Order By: Relevance
“…No increase in major birth defects or skeletal abnormalities was observed. In long‐term follow‐up, only two infants exposed in utero to bisphosphonates were tested; they were shown to have normal bone density at five and six years of age, respectively 38. In contrast, Losada et al observed a 20% rate of congenital malformations in children of patients with autoimmune rheumatic diseases taking bisphosphonates combined with other medications 33.…”
Section: Discussionmentioning
confidence: 99%
“…No increase in major birth defects or skeletal abnormalities was observed. In long‐term follow‐up, only two infants exposed in utero to bisphosphonates were tested; they were shown to have normal bone density at five and six years of age, respectively 38. In contrast, Losada et al observed a 20% rate of congenital malformations in children of patients with autoimmune rheumatic diseases taking bisphosphonates combined with other medications 33.…”
Section: Discussionmentioning
confidence: 99%
“…Otuz gün sonra asemptomatik olan hastanın tedavi sonrası 3. aydaki kontrol MRG'de eski kırıklarda iyileşme görülürken 6. ve 12. ayda tekrarlanan DEXA ölçümlerinde lomber bölgede daha fazla olmak üzere KMY değerlerinde belirgin yükselme tespit edilmiş. Bir başka GİO tanılı olguya (20) siklik etidronat tedavisi (her 3 ayda 400 mg/gün 14 gün) verilmiş. Konsepsiyondan 3 ay önce son dozu almak üzere, etidronat tedavisi devam ederken 2 kez daha gebe kalan hastanın normal geçen gebeliklerinin yanı sıra yenidoğan çocuklarında hipokalsemi veya herhangi bir iskelet anomalisi gelişmemiş.…”
Section: Discussionunclassified
“…The outcome of pregnancy was positive, though no further details were given about neonatal health. 12 Following that report, Athimulam et al 13 and Vujasinovic-Stupar et al 14 presented the outcome of 2 more cases of BPs-exposed women due to PO. In the first case, 13 a 34-year-old woman treated with alendronate after her second delivery, discontinued BPs at the beginning of her third pregnancy.…”
Section: -Cases Of Women Treated With Bps Due To Pregnancy-associatedmentioning
confidence: 97%